2022
DOI: 10.1128/mbio.01635-22
|View full text |Cite
|
Sign up to set email alerts
|

CDC50 Orthologues in Plasmodium falciparum Have Distinct Roles in Merozoite Egress and Trophozoite Maturation

Abstract: Malaria morbidity arises due to successive rounds of replication of Plasmodium parasites within red blood cells. Mature daughter merozoites are released from infected erythrocytes to invade new cells in a tightly regulated process termed egress.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Deletion of CDC50B does not impair asexual blood stages or gametogenesis. However, two other CDC50 proteins are encoded by Plasmodium , and it is possible that deletion of CDC50B is complemented by another CDC50 protein as suggested in ( 39 ). In support of this hypothesis, it was recently shown in T. gondii that multiple CDC50 proteins interact with the same P4-ATPase ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of CDC50B does not impair asexual blood stages or gametogenesis. However, two other CDC50 proteins are encoded by Plasmodium , and it is possible that deletion of CDC50B is complemented by another CDC50 protein as suggested in ( 39 ). In support of this hypothesis, it was recently shown in T. gondii that multiple CDC50 proteins interact with the same P4-ATPase ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…8). CDC50B is likely involved in GCα folding or trafficking during both stages but its deletion is possibly complemented by another CDC50 protein ( 39 ). GEP1 is only expressed in gametocytes where it is essential for GCα basal activity ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two parasite proteins that likely act upstream of GCα were recently shown to be involved in efficient blood‐stage egress. The membrane protein cell division control protein 50B (CDC50B) was proposed to be required for efficient cGMP synthesis by GCα (Patel et al, 2022), and P. falciparum parasites lacking CDC50B expression took longer to egress. Another protein that was recently shown to act early during blood‐stage egress is the P. falciparum protein phosphatase 1 (PP1) (Paul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the invasion process has indicated that the nascent PVM that surrounds the parasite during and immediately after invasion is derived of host erythrocyte membrane (Geoghegan et al, 2021), but the origin of the phospholipids required for the formation and expansion of the other internal membranes is unclear. The parasite can take up exogenous phospholipids (Moll et al, 1988;Haldar et al, 1989;Fraser et al, 2021;Patel et al, 2022), which the parasites may use to build these compartments, but the parasite also grows in the absence of exogenous phospholipids when the medium is supplemented with fatty acids (Divo et al, 1985;Mitamura et al, 2000;Asahi et al, 2005;Mi-Ichi et al, 2006, 2007Asahi, 2009). Hence, the parasite appears able to fulfil its phospholipid requirement solely with phospholipids that it synthesizes itself (Vial et al, 1990).…”
Section: Introductionmentioning
confidence: 99%